Switching to the inflation targeting regime: Does it necessary for the case of Egypt? - Ibrahim L. Awad (Charles University in Prague, Institute of Economic Studies (IES), 2008)
The purpose of this paper is to answer the question of whether the switching to the Inflation Targeting (IT) regime is necessary for the Egyptian case or not? Our judgment of applying IT regime in the Egyptian economy is established on doubled criterion. That is, the practical experience of the inflation targeters, and the efficiency of Monetary Targeting Regime (MTR) in the case of Egypt. Defining the efficiency of a monetary policy regime by the efficiency of the embedded nominal anchor to send the right message to all practitioners about the potential behavior of the price level, I assessed the efficiency of MTR in Egypt by measuring; whether there is a relationship between money and prices, the stability of the velocity of circulation, and the stability of the demand for money function. The study concluded that MTR is not efficient to tie down individuals expectations about the future path of inflation in Egypt. Taking into account that IT regime is a way to reform monetary policy and it does not worsen economic performance it becomes necessary for Egypt to switch to the IT regime once the prerequisites for IT regime have been met.
Keywords: E31; E41; E51; E52; E58; E59; 330; inflation targeting; demand for money function; monetary policy in Egypt; Inflationssteuerung; Geldpolitik; Ägypten